+0  
 
0
69
2
avatar

The difference of the roots of the quadratic equation $x^2 + bx + c = 0$ is $|b - 2c|$. If $c \neq 0$, then find $c$ in terms of $b$.

 Nov 17, 2020

Best Answer 

 #1
avatar+97 
+2

Hello Guest!

 

By the quadratic formula, $x = \frac{-b + \sqrt{b^2 - 4c}}{2}, \frac{-b - \sqrt{b^2 - 4c}}{2}$. The difference of these is $\frac{2\sqrt{b^2 - 4c}}{2} = \sqrt{b^2 - 4c}$. Setting this equal to $|b - 2c|$, it follows that (after squaring) $b^2 - 4c = (b-2c)^2 = b^2 + 4c^2 - 4bc$. Thus$$0 = 4c^2 + 4c - 4bc = 4c(c - b + 1).$$As $c \neq 0$, it follows that $c = \boxed{b - 1}$.

 

Hope this helped! angel

 Nov 17, 2020
 #1
avatar+97 
+2
Best Answer

Hello Guest!

 

By the quadratic formula, $x = \frac{-b + \sqrt{b^2 - 4c}}{2}, \frac{-b - \sqrt{b^2 - 4c}}{2}$. The difference of these is $\frac{2\sqrt{b^2 - 4c}}{2} = \sqrt{b^2 - 4c}$. Setting this equal to $|b - 2c|$, it follows that (after squaring) $b^2 - 4c = (b-2c)^2 = b^2 + 4c^2 - 4bc$. Thus$$0 = 4c^2 + 4c - 4bc = 4c(c - b + 1).$$As $c \neq 0$, it follows that $c = \boxed{b - 1}$.

 

Hope this helped! angel

ETERNITY Nov 17, 2020
 #2
avatar+114221 
0

Very nice, Eternity    !!!!

 

cool cool cool

CPhill  Nov 17, 2020

20 Online Users

avatar
avatar